TEACHING ENGLISH ON THE BASIS OF MODERN TECHNOLOGIES - RADJAPOVA FERUZA ABDULLAEVNA; IBADULLAYEVA МALIKA KHAMDAMBEK QIZI (Western European Studies, 2024)
Flipped classroom technology is becoming increasingly popular in higher education is ongoing and is sometimes controversial. Many professional educators have highlighted the potential benefits of this model. Early studies of implementation were primarily positive. The rationale for changing classroom style is to increase student engagement with content, increase faculty contact time with students, and improve learning. Flipped classroom technology is a type of blended learning in which students are introduced to a topic at home and practice working through it at school. In this article, different from the traditional teaching process, using modern pedagogical technology (inverted classroom technology), the issues and steps of improving the efficiency of the lesson and students are covered.
Keywords: technology; innovative; teacher